O perfil de saúde de estudantes universitários: um estudo sob o enfoque da psicologia da saúde - Silva, Rachel Rubin da (2011)
College students can be characterized as a group deserving special attention, given its evolutionary moment, usually the transition from adolescence to adulthood and experiencing a phase of adaptation to new demands and challenges of higher education context (POLYDORO, 2000). This study aims to investigate quality of life, psychological well-being and relational characteristics of college students. The sample consisted of 367 college students. We conducted a study that was crosssectional, descriptive, of correlational character, quantitative and qualitative in approach. The instruments were a demographic data sheet, the OMS World Health Organization Quality of Life (WHOQOL-bref), the General Health Questionnaire (GHQ-12), and the Bell Object Relations and Reality Testing Inventory (BORRTI-O). Results were obtained through descriptive and inferential statistical analysis using the statistical package SPSS 13.0. The sample comprised 217 women (59.1%) and 150 men (40.9%) with mean age of 22.8 years. Among the main results, we underline the high rate of psychological distress presented by sample where 48.8% of participants presents: psychic suffering worthy of attention; average indices of quality of life, with a particular harm in the field of environment and an average of 15.9% in relational pathology. The instruments showed significant correlations between rates of psychological distress, quality of life and relational features, emphasizing the importance of knowing such information to a global understanding of the college student. Furthermore, we emphasize the importance of programs designed to provide health care to students for purposes of prevention and health promotion in the university context.